The Kalahari Peoples Fund: Activist Legacy of the Harvard Kalahari Research Group - Biesele, Megan (Anthropologica, 2022)
The multidisciplinary Harvard Kalahari Research Group (HKRG) led by Richard Lee and Irven DeVore was expanded in 1973, after a decade of interlocking anthropological research projects in Botswana, to include an activist non-profit organization, The Kalahari Peoples Fund (KPF). KPF is one of the oldest anthropological advocacy groups in North America. Now past its 25-year anniversary, KPF remains active with a newsletter, a website, and substantial ongoing projects in community-based education and natural resource management in Kalahari communities in both Botswana and Namibia. In large part the success of KPF is due to the length and depth of the ethnographic studies—by Richard Lee and collaborating colleagues—that have underwritten it through out its history